The Influence of the Digital Era on the Transformation of Personnel Administration Policy at SMP Negeri I Gebang - Krisna Pratiansyah, Panji; Khumayah, Siti; Rohida, Leni (Jurnal Polisci, 2025)
Background. Advances in digital technology, including the management of staff in educational institutions, have led to significant changes in various aspects of life. For effective and open employee management, the use of IT-based systems has become important in the modern era. As formal educational institutions, schools are unaffected by these digital advancements, which include attendance data management, performance appraisals, employee promotions and mutations, and monitoring of teacher performance data. Aims. This study aims to analyze the influence of the digital era on the transformation of personnel administration policies at SMP Negeri 1 Gebang. The research approach used was ex-post facto quantitative, with a population and sample of 21 teachers taken using census techniques. Data collection through Likert scale questionnaires and documentation, Jamovi software is used to analyze the data. Methods. The research approach employed was an ex-post facto quantitative study, with a population and sample of 21 teachers selected using census techniques. Data collection was conducted through Likert scale questionnaires and documentation. Jamovi software was used to analyze the data. Result. The results of descriptive statistical analysis showed that the average score of digital administration policy was 30.4 and teacher performance was 16.0, with a relatively homogeneous data distribution. The instrument's reliability test yielded a Cronbach's Alpha of 0.847, which is in the category of very reliable. The validity test, conducted using Pearson correlation, revealed a strong and significant positive relationship (r = 0.755; p < 0.001). Conclusion. A simple linear regression analysis yielded an equation Y = -2.119 + 0.595X with a coefficient of b = 0.595 and p < 0.001, which means that there is a positive and significant influence between the digital era and the transformation of personnel administration policies. A coefficient of determination (R²) of 0.570 indicates that digital era variables can explain 57% of the variation in personnel administration policy transformation. Implementation. This study concludes that the application of digital technology contributes significantly to changes in personnel administration policies, encouraging more efficient, transparent, and accountable processes in the school environment